Self-Organisation and the Co-Production of Governance: The Challenge of Local Responses to Climate Change - Atkinson, Rob (2018)
The arena of locally embedded and engendered responses to climate change offers a particularly fruitful and challenging space in which to scrutinise the encounters between established forms of governance and knowledge as they become entwined with locally generated forms of self-organisation. The issue of climate change offers a particularly fertile case for study because to date it has largely been dominated by state and market-based responses and associated forms of governance selectively articulated with knowledge generated through scientific and expert modes of knowledge. The central focus of the article is on identifying the variegated forms of understanding associated with the groups we researched and how they drew upon/utilised knowledge (knowledge-in-action) vis-à-vis the governance of ecological politics and environmental governance. The article draws on case studies of self-organising locally based groups in Germany, the Netherlands and the United Kingdom that are addressing climate change, in a broad sense, within their locality. These groups represent a range of responses to the issue and associated modes of action, exhibit different levels and forms of ‘organisation’ and may challenge more established forms of governance and knowledge in different ways.